2019
DOI: 10.5603/ah.a2019.0006
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor as a marker of endothelial dysfunction in poly- and comorbidity: focus on hypertension, type 2 diabetes mellitus and subclinical hypothyroidism

Abstract: Background. The goal of our study was to investigate the content and particularities of change of vascular endothelial growth factor-A (VEGF-A) levels as a marker of endothelial dysfunction (ED) in patients with hypertension (HT) with or without type 2 diabetes mellitus (T2DM) and with or without subclinical hypothyroidism (SH). Material and methods. Two hundred and eleven patients with hypertension stage II were divided into 3 groups: Group 1-with HT (n = 55); Group 2-with AH and T2DM (n = 97); Group 3-with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In our previous study, we have shown that mutually aggravating effect of endothelial dysfunction, dyslipidemia, hyperglycemia and insulin resistance on the clinical course of HTN and T2DM may exist [23]. In this study, differences in TC, LDL-C, HOMA-IR and SBP were observed with relation to 8-OHdG plasma levels.…”
Section: Discussionsupporting
confidence: 48%
“…In our previous study, we have shown that mutually aggravating effect of endothelial dysfunction, dyslipidemia, hyperglycemia and insulin resistance on the clinical course of HTN and T2DM may exist [23]. In this study, differences in TC, LDL-C, HOMA-IR and SBP were observed with relation to 8-OHdG plasma levels.…”
Section: Discussionsupporting
confidence: 48%
“…There is a strong evidence of endothelial activation in symptomatic malaria including uncomplicated and severe malaria [ 37 , 38 , 43 ], while similar data in asymptomatically infected persons are limited. In this study, we determined whether plasma levels of the angiogenic marker VEGF-A and its receptor VEGFR2 as well as the endothelial activation marker ICAM-1 are increased in asymptomatic children with either microscopic parasitemia or submicroscopic parasitemia compared with uninfected age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of endothelial activation molecules have been associated with adverse outcomes in diseases like diabetes, resulting in endothelial dysfunction and organ damage [ 43 , 53 , 54 ]. The recent malaria–high-blood pressure hypothesis, which seeks to determine the effect of chronic endothelial activation in malaria on the development of cardiovascular diseases, may suggest that endothelial cell activation in asymptomatic infection is an early indicator of some potential health complications [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HTN, it has been shown that VEGF levels are often increased, promoting vascular wall remodeling and suggesting a contribution of abnormal angiogenesis to the pathogenesis of HTN and hypertension-related complications [106][107][108]. Tsai et al demonstrated significantly higher VEGF levels in patients with HTN and retinopathy compared to normotensive subjects, and suggested that plasma VEGF levels may be a useful biomarker for the early detection of microvascular damage [75].…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…Tsai et al demonstrated significantly higher VEGF levels in patients with HTN and retinopathy compared to normotensive subjects, and suggested that plasma VEGF levels may be a useful biomarker for the early detection of microvascular damage [75]. Plasma VEGF has also been shown to be a useful early marker of endothelial dysfunction, even before active intravascular inflammation had developed [75,106]. A clinical pilot study by Belgore et al showed a significant reduction in plasma VEGF under the influence of 2 months of antihypertensive therapy [108].…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%